2012
DOI: 10.1007/978-3-642-34109-0_32
|View full text |Cite
|
Sign up to set email alerts
|

Computing Discriminating and Generic Words

Abstract: Abstract. We study the following three problems of computing generic or discriminating words for a given collection of documents. Given a pattern P and a threshold d, we want to report (i) all longest extensions of P which occur in at least d documents, (ii) all shortest extensions of P which occur in less than d documents, and (iii) all shortest extensions of P which occur only in d selected documents. For these problems, we propose efficient algorithms based on suffix trees and using advanced data structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…In [8] the authors showed how the problem of identifying minimal discriminating words can be reduced to orthogonal segment intersection problem. In this article, we rely on this key insight for both problems under consideration and use the result summarized in the lemma below for segment intersection.…”
Section: Segment Intersection Problemmentioning
confidence: 98%
See 4 more Smart Citations
“…In [8] the authors showed how the problem of identifying minimal discriminating words can be reduced to orthogonal segment intersection problem. In this article, we rely on this key insight for both problems under consideration and use the result summarized in the lemma below for segment intersection.…”
Section: Segment Intersection Problemmentioning
confidence: 98%
“…In this section, we first review a linear space index, which is based on the ideas from the previous results [8]. Later we show how to employ sampling techniques to achieve a space efficient solution.…”
Section: Indexes For Computing Maximal Generic Wordsmentioning
confidence: 99%
See 3 more Smart Citations